ANALISIS EVALUASI PELAKSANAAN PROGRAM BIMBINGAN DAN KONSELING BIDANG SOSIAL DI SMA NEGERI 9 PONTIANAK - Juniarti, Ely; Endang, Busri; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractGuidance counselor teacher have important role in developing social guidance to leaners in the development ofÂ ability and overcoming social problems in school and community in working together, interacting with friend of the same age and adults. Evaluation of the implementation of social guidance and counseling program is very important in order to know the positive and negative impacts of good relations both at school and outside school and to know the achievement of the program implementation. The low evaluation of the implementation of the social guidance program will lead to low achievement between programs and implementation. For that hope in the achievement of guidance and counseling program in the field of social, researcher reviewed the evaluation of the implementation of social guidance and counseling program in SMA Negeri 9 Pontianak.The problem in this research is â€œhow the evaluation of the implementation of social guidance and counseling program in SMA Negeri 9 Pontianak?â€. This study aims to obtain a description and objective information about the evaluation of the implementation of social guidance and counseling program in SMA Negeri 9 Pontianak.The research method used is naturalistic qualitative method. The sample of this research is two gudance and counseling teachers. Data collection techniques, interviews, and documentation. The result of data analysis indicate that evaluation of implementation and social counseling programs is done well. It is expected that the gudance counselor teachers to improve the evaluation of the implementation of social guidance and counseling programs in order to know the positive and negative impacts ofÂ the intercommunication and to know the achievement of the program.Â Keyword: Program Evaluation, Social Field.